Introduction to digital image processing - Pratt, William K. (Boca Raton, [Florida] : CRC Press, Taylor & Francis Group, 2014)
'This book contains English language narratives of important image processing operations, from which a student is expected to create executable versions of the operations using C language programming, calls to an image processing library furnished with the book, a furnished PIKSTool interactive package or the widely supported MATLAB interactive package. Executable versions of each narrative operation are furnished so that a student can visualize the result of each operation.'--
Includes bibliographical references : (p. 717-724) and index.
Keywords: Image processing -- Digital techniques; TECHNOLOGY & ENGINEERING / Imaging Systems; Image processing -- Digital techniques